Profil Komformitas Teman Sebaya Berdasarkan Faktor Demografi - Ranni Rahmayanthi; Ilfiandra Ilfiandra; Syamsu Yusuf (Indonesian Journal of Educational Counseling, 2020)
PEER PERFORMANCE PROFILE BASED ON DEMOGRAPHIC FACTORS. The purpose of this study was to determine the conformity profile peers based on demographics socioeconomic status. Participants in this study were 123 students junior high school consist of 39 regulars student and 86 “binalingkungan” (low economic) students. The average age of participants was 12-15 years. This research approach using quantitative approach, types of research using a cross sectional survey. The instruments used was a scale conformity peers who developed the theory Brendt use any form of semantic differential scale with alternative answers 1-6 (1 = very inappropriate, 6 = very appropriate). Data were analysed using analysis Mann-Whitney U with a score of 1488.00 and a significance probability value of 0.414. Because the probability of significance 0.414> 0.05, the results showed that there was no difference conformity peers in the student of low socioeconomic status and students socioeconomic status of middle to top.